Innovative Strategies in Fermented Food Production: Harnessing Genetic and Metabolic Engineering of Lactic Acid Bacteria - Ahmad, Saleem; Ahmed , Tanveer; Samad , Abdul; Sohaib Ur Rehman; Muhammad Ghalib (Dialogue Social Science Review (DSSR), 2024)
Fermentation has been a time-honored process used since ancient times to improve the sensory properties and preservation of food. Microorganisms have been used for various types of fermented food because of their outstanding ability to serve as cell factories. Lactic acid bacteria (LAB) play crucial roles in fermentation products ranging from traditional milk products to fruits and vegetables. Recent advances in recombinant DNA technology and genetic engineering via engineered lactic acid bacteria (LAB) have led to significant improvements in the food industry. This review aims to present the ability of engineered LAB to improve and enhance both the quality and the quality of fermented products. We discuss the role of GM-LAB in cheese production and ripening; ethnic fermented foods derived from milk, vegetable and meat; the role of food-derived bioactive compounds such as amino acids, SCFAs and EPS in nutrition and health; the synthesis of flavoring and aroma molecules such as acetaldehyde, diacetyl, and sweeteners such as sorbitol and mannitol;, etc. Finally, we present the ability of GM-LAB as probiotics, in terms of bio preservation, food safety and food waste conversion into biofuel.